TEKNOLOGI SEBAGAI SARANA PEMBELAJARAN YANG EFEKTIF DI SEKOLAH DASAR: STUDI KASUS SDIT AL-FATH - Wiwi Nurjanah; Dhea Lionita, Indri Ardiyanti, Camelia Putri, dan Bramianto Setiawan (CV. ADIBA ASIHA AMIRA, 2024)
The development of technology in modern times today in the era of the 21st century, is experiencing very rapid development. Technology has a very important role for everyone. The use of technology as a learning tool is needed by educators. But the problem is that not all educators use technology as a means of learning, there are several factors that influence this. The utilization of technology as a learning medium is intended to make learning in the classroom more effective and efficient, and to make students happy and enthusiastic in learning because learning is not only based on books. This research aims to find out and see whether this technology-based learning media is effectively used by educators in the teaching and learning process in elementary schools. In this study, researchers used a qualitative method with the type of literature study and observation conducted through classroom observations and interviews with one of the SDIT Al-Fath teachers in Cibitung. And from the results of the research that has been done, it states that technology-based learning media is very effective in being used by educators in the teaching and learning process. In this sophisticated era, it is expected that educators use technology as a means of learning in accordance with the times and the needs of their students.